Case Report: Medical Aspect, Growth, and Quality of Life in Children with 46,XX Testicular Disorder of Sex Development (DSD) - Rochmah, Nur; Faizi, Muhammad; Andriani, Irwina Rahma; Pasulu, Soraya Salle (Folia Medica Indonesiana, 2018)
46,XX testicular disorder of sexual development (DSD) is characterized by male phenotype with 46,XX karyotype. The incidence rate is 1:25,000 in male newborn. Infants with ambiguous external genitals will be confronted with issue of gender assigment and may result in a stressful condition in the parents. Since gender assignment is inevitable, several factors should be considered in DSD management. The management approach for children born with DSD is individualized and multidisciplinary. Gender assignment aims to facilitate the patient to obtain the best quality of life. Adaptation of children with 46,XX testicular DSD as a determinant of quality of life is also influenced by psychological and family conditions. The purpose of this report was to observe medical growth and development aspects of the child with 46,XX terticular DSD as indicated by the aspects of growth and development, and health related quality of life, as well as the influential aspects. PA, 18 months, was diagnosed with 46,XX testicular DSD. The patient routinely visited to endocrinology clinic, urologic surgery, and child psychiatry clinic from the age of 6 months. The parents decided to raise patient as male. The patient had undergone surgery for hypospadias correction, hormone injections, child growth monitoring, and psychological monitoring (medical records of Dr. Soetomo Hospital, Surabaya in 2015). Management should consider individual and multidiciplinary accompaniment of the patient and parents, the importance of group support, and follow-up to adulthood, as well as possible longterm outcomes that will occur in the future so that the patients and the parents need to be prepared.